Spatial Effect Analysis of Total Financing and Factors Affecting Them at Banking in Indonesia - Idris, Aditya; Didiharyono, Didiharyono (Journal of Mathematics and Applied Statistics, 2023)
This study aims to formulate a pattern of spatial linkages between provinces in Indonesia based on the amount of bank financing through the influencing factors, namely third-party funds (DPK), Non-Performing Financing (NPF), MSME financing loans and GRDP. The data used is 2021 data. By using the Spatial Regression method with Moran' s I Test, it will look for relationships and inter-regional (spatial) relationships in the amount of bank financing based on the observed factors. From the results of data analysis, the Moran's I value obtained is 0.4439. Then based on the test results |2,2444|>1.96, the decision making according to the existing hypothesis is H0 rejected. It can be concluded that there are spatial dependencies between provinces based on the amount of bank financing in each province according to the observed factors, namely DPK, NPF, MSME financing credit and GRDP. The expected output in implementing this developed strategy is to increase the amount of banking financing that is evenly distributed in each province in order to achieve the objectives from the economic aspect while taking into account the benefits for banking institutions. The improvement in the economic aspects in question includes increasing the usability of money, increasing the usability of goods, maintaining the country's economic stability and as a bridge to increase national income.